Study on the rearrangeability of 3n-1 stages shuffle-exchange network - GE Fang-bin1; ZHANG Tao1; SONG Jin-yu1; ZHAO Min1; CHEN Wei-hua2 (Tongxin xuebao)
Rearrangeability is an essential issue in study of SE（shuffle-exchange） network and its application.Currently,there are no practical methods to realize rearrangeability of SE networks when n>4.Based on the fact,a policy to realize the rearrangeability was proposed in 3n-1 stages Omega network.In the policy,the problem of constructing no conflict routing was translated into how to rearrange routing inputs and decompose routing sequence.A method to rearrange routing inputs by adjusting conflict nodes and expanding routings without conflict was offered.The feasibility of ex-panding routings without conflict was proved,and an algorithm of expanding routings was provided.The rearrangeability of Omega network was first realized when n=5.If Ge conjecture on decomposing routing sequence is constructively proved,how to realize the rearrangeability of the 3n-1 Omega network would be perfectly solved by the policy.